INFLUENCE OF BRAND AWARENESS AND PERCEIVED QUALITY TOWARD INTEREST IN REPURCHASING DAIRY PRODUCT ANLENE - Astuti, Widi; Kurniati, Dewi; Maswadi, Maswadi (Fakultas Pertanian Universitas Tanjungpura, 2019)
ABSTRACTEarly cases of bone loss or osteoporosis in Indonesian are higher than the world average, because two out of five Indonesians are at risk for this disease, while the world average is only one in three people at risk of developing osteoporosis. So that public awareness needs to be raised about the dangers of osteoporosis. Preventing osteoporosils can be done by drinking Anlene's milk. The purpose of the study was to analyze the effect of brand awareness and perceived quality on the interest in repurchasing Anlene milk products, in 150 respondents selected purposively. Data analysis using Structural Equation Modeling (SEM) with Lisrel software. The results showed that brand awareness has a positive effect on repurchase interest, with the most influential indicators being the peak of the mind. Then the perception of quality has a positive effect on repurchase interest, with the most influential indicators being product characteristics. This can be used by producers to pay more attention to brand awareness through peak thinking and perceived quality through product characteristics so that consumers always re-purchase Anlene milk products.Keywords: brand awareness, perceived quality, interest in repurchasing, Anlene dairy products, Structural Equation Modeling (SEM).